COORDINATION AMONG LOCAL AGENCIES IN DECENTRALISED FISHERIES EXTENSION: COMPARATIVE PERCEPTION OF EXTENSION OFFICERS IN JAVA, INDONESIA - , Waridin (JOURNAL OF COASTAL DEVELOPMENT, 2002)
This study is intended to describe the conditions of coordination among local agencies involved in the implementation of decentralisation policy in fisheries extension in Java, Indonesia. In addition, this study is also aimed at assessing the effectiveness of the policy implementation, and determines its relationship to coordination among local agencies involved. Population of this study comprised all fisheries extension officers attached with Rural Extension Centres (RECs). A multi-stage random sampling method was utilised for selecting the subjects for the study. A total of 50 officers at 10 districts in three provinces were covered in this study. Data were collected during January to March 1998 by using interview and self-administered techniques. Descriptive statistics and correlation analyses were used in the study. The majority of officers confirmed that the RECs were not coordinated with related agencies involved in implementation of the policy. This indicates that policy implementation is not effectively done. Coordination among agencies involved was found to correlate highly to the effectiveness of policy implementation. Intensity of coordination among agencies involved in the policy implementation needs to be improved. A clearer directive for functions, responsibilities and relationships among agencies involved might help in strengthening the current coordination functions.